Development of student worksheets for algebra material based on an open-ended approach to support reasoning skills - Fadhillah, Mulayyin Azhar; Toyib, Muhamad (Universitas Islam Negeri Raden Intan Lampung, 2024)
The Open-Ended approach allows students to develop mathematical reasoning abilities. Using an Open-Ended approach allows students to find various solutions to their problems. This study aims to develop mathematics Student Worksheets based on Open-Ended approaches to valid and practical algebra material and to discover that the mathematics Student Worksheets created can support students' reasoning abilities. This development research is based on the 4-D development model. The study subjects were in the 7th grade at Muhammadiyah 3 Sambungmacan Junior High School. Research data was obtained through observation, questionnaires, and reasoning ability tests. Data analysis techniques include validity tests, practicality tests, and effectiveness tests. The results of the data analysis show that the quality of Student Worksheets seen from the aspect of validity is included in the valid category with an average score of 3.11, based on expert assessment. From the practicality aspect, the Student Worksheet is declared practical based on the results of teacher responses with an average score of 3.00 and student responses with an average score of 3.22. The effectiveness of Student Worksheets based on the results of the reasoning ability test obtained a score of 57.65%, including being in the category of quite effective. Therefore, the Student Worksheet is feasible, practical, and quite effective to use.